The relationship between survival rate of melanoma patients and selected clinical and morphological parameters - Teresiak, Marek; Krenz, Roman; Grodecka-Gazdecka, Sylwia; Kycler, Witold (Contemporary Oncology/Współczesna Onkologia, 2001)
The aim of the study was the retrospective assessment of some morphological and clinical prognostic factors in cutaneous primary melanoma and their association with the survival rate. 124 patients operated in the II Surgery Ward of the Great Poland Cancer Center between 1990 and 1994 were analyzed. The prognostic value of clinical data, such as age, gender, tumor location have been evaluated. The assessment of histology was performed on archival histopathological specimens in terms of: the thickness of melanoma (measured by Breslow method), the level of invasion measured according to Clark, a histological type, lymphocyte infiltration, the presence of regression symptoms, ulceration, the existence of satellites and lymphatic metastases. In addition to the above the role of the primary surgical treatment in conjunction with prognostic parameters was evaluated. This clinical and histopathological data were correlated with a survival rate. Survival analysis was performed using the Cox proportional hazards regression model. The most predictive factor for the recurrence and prognosis of melanoma in the study was the existence of lymphatic metastases.